PERFORMANCE EVALUATION OF ROOF-TOP PV SYSTEMS IN THE AREA OF KAVALA NORTH GREECE - FANTIDIS, JACOB G; Constantinos, Potolias; Bandekas, Demetrios; Kogias, Panagiotis; Stathakis, Efthymios; Karakoulidis, Konstantinos; Meresentoglou, K. (Journal of Applied Engineering Science, 2015)
The continuously growing demand for electricity and the need to develop Renewable Energy Sources (RES), pushed the modern world to develop Photovoltaic (PV) systems. An evaluation of performance of photovoltaic power systems has conducted, aiming to analyze the causes of performance reduction of the systems. During the years 2010 - 2013 where theoretical is a period which was described as «fever of photovoltaic» systems installation in Greece. There were so blatant manufacturing defects mainly to the roof-top PV systems. Studding their location and construction method, radically different, even in neighboring systems we find that the reflection on the performance conditions are reasonable and easy to understand. This is the reason that leads us to make a research study regarding the performance differences of the roof-top PV systems and the causes of them. Mainly we deal more with the systems low performance ≤ 10KW, because they are more economical and interesting. In this paper, a study for the area of prefecture of Kavala, Greece is analyzed.